Interlanguage Errors In Writing Descriptive Text Made By Students Of SMA Negeri 1 Sumberlawang. - Anggoro, Ari; , Prof. Dr. Endang Fauziati, M.Hum; , Dra. Dwi Haryati, M. Hum (2013)
This study aims at describing the interlanguage errors made by the students of SMA Negeri 1 Sumberlawang in their written descriptive text; identify the types of lexical errors, syntactical errors and discourse errors; describing the frequency of each type of errors; explain the dominant type of error; identify the source of error and explain the pedagogical application in teaching learning English as foreign language. The type of this research is descriptive qualitative research. Elicitation technique and documentation are methods used by writer to collect the data. There are three steps to collect data, namely: the writer gets the data of English composition made by the students from the teacher, the writer identifies and marks the errors within the text made by students, the writer classifies the errorneous sentences into a list and used them as the data. The collected data are analyzed by using James classification of errors theory, Slamet the frequency of type of error theory and Brown source of errors theory. The results of the research show that the students of SMA Negeri 1 Sumberlawang still make 139 errors in their compositions. The writer finds that from 1139 data, there are three classifications of error based on the combination of linguistic category and surface strategy taxonomy. There are lexical errors consist of 7, 91% including: wrong spelling 4, 32% and use Indonesian word/ code switching 3, 60%. Errors on syntactical errors consist of 75, 54% including: phrase 11, 51%, the use of verb 34, 53%, pronoun 20, 15%, article 5%, literal translation 2, 16%, conjunction 1, 44% and preposition 0, 72%. And errors on discourse consist of 16, 55% including component of discourse 9, 35 and generic structure 7, 19%. It is derived from 27 types of error. The highest frequency of errors that the researcher found is misordering of words in a phrase. There are 12 or 8, 63% errors found from the total errors. The researcher also finds 2 dominant sources error, namely: interlingual transfer and intralingual transfer.